ANALISIS MANAJERIAL PEMBELAJARAN GRAMATIKAL BAHASA ARAB DI PONDOK PESANTREN SALAFIYYAH PUTRA DARUL ULUM PUJON, MALANG: Managerial Analysis of Arabic Grammatical Learning at the Salafiyyah Putra Darul Ulum Islamic Boarding School Pujon, Malang - Basri, Hasan (Uniqbu Journal of Social Sciences, 2021)
This study aims to describe managerial learning form. Arabic grammatical language in Salafiyyah Putra Darul Ulum Islamic boarding school, explains problem indicators of its success. This study used qualitative descriptive method with data collection using observation, interview and documentation techniques. Data validition of this study are used triangulation method. Meanwhile, data analysis are used Miles and Huberman model which includes data reduction, display data, conclusion and verification. Subjects in this study are 53 students that divided into IV, V, VI MI, and I, II, and III Mts. Result of this study showed that managerial process of Arabic grammatical learning at Darul Ulum Islamic boarding school. There is planning process including daily formulation, weekly, and annual agenda. Implementation of daily agenda is sorogan form, weekly agenda in lalaran form, and annual agenda in memorization form and book of reading competition. Meanwhile, evaluation is carried out into three stages, namely weekly, monthly and annual stages. However, managerial learning found problem in difficulty form of using sterile meaning method to new santri who had ethnic backgrounds other than Javanese. Indicator of success is activeness of students in participating in various Bahtsul Masa'il forums.